The relationship between symptoms of gender dysphoria and social anxiety in transgender young adults: a network analysis - Jiaqi Li; Yi Feng; Wenbang Niu; Shicun Xu; Yajun Bu; Yuanyuan Wang (BMC Psychiatry)
Abstract Background Gender dysphoria and social anxiety co-occur in transgender young adults,whereas their underlying influencing mechanism remains limitedly explored. Aims This study attempted to investigate the symptomatic relationships between these two mental illnesses in transgender young adults and explore heterogeneous network connections in various transgender groups. Methods This study was from a large-scale cross-sectional survey that recruited 117,769 Chinese college students. After screening gender identity, we divided 2,352 transgender participants into three groups: transgender men, transgender women, and non-binary identities. The Utrecht Gender Dysphoria Scale-Gender Spectrum measured gender dysphoria, and the Social Anxiety Subscale of the Self-Consciousness Scale measured social anxiety. Network analysis and directed acyclic graphs explored the relationships between symptoms of gender dysphoria and social anxiety among transgender young adults. Results Transgender young adults in this study consist of 1,223 transgender men, 538 transgender women, and 591 non-binary identities. “Unhappy in physical characteristics” and “Hopeless” were the most crucial central symptoms; “Distressing body functions” and “Hard time working” were the main bridge symptoms in network structures of gender dysphoria and social anxiety. In transgender women’s network structure, “Distressing bodily functions” was positively connected to “Hard time working,” while it was positively linked to “Nervous speaking” in that of the non-binary group. Discussion Feeling unhappy with physical characteristics and hopelessness are crucial influencing factors in transgender young adults’ co-occurring symptoms of gender dysphoria and social anxiety. Since symptomatic connections were heterogeneous across the three transgender groups, diverse tailoring interventions combined with social efforts are required to buffer against the co-occurrence of gender dysphoria and social anxiety.